The adoption of the State-Trait Anger Expression Inventory (STAXI-2) in the Greek language - Μπεζεβέγκης Ηλίας; Ντάλλα Μαρίνα; Γκαρή Αικατερίνη; Χ. Καραδήμας Ευάγγελος (Psychology: the Journal of the Hellenic Psychological Society, 2008)
The abstract is available in the PDF